Master singers advice from the stage - George, Donald 1955-; Mauro, Lucy (Oxford University Press, 2015)
Donald George and Lucy Mauro interview twenty-one of today's top international opera singers. With questions centred on what must be done to perform on the major stages of the world, the artists offer practical and concise advice on a variety of performance-related topics.
Keywords: Singing / Vocational guidance; Singers / Interviews; Singers / Biographies; Berühmte Persönlichkeit; Bühnengesang; Sänger; Gespräch